Polyhydroxyalkanoates (PHAs) production from saponified sunflower oil in mixed cultures under aerobic condition - Mohd. Fadhil, Mohd. Fadhil; Ujang, Zaini; Van Loosdrecht, Mark; Ahmad, Mohd. Azlan (Penerbit UTM Press, 2008)
A laboratory study was conducted to assess the optimal conditions for polyhyroxyalkanoates (PHA) production using saponified sunflower oil (SO). The system was operated under continuous sequential phase of growth and accumulation conditions. The main purpose of using saponified SO was to improve the quality of PHA constituents (e.g. copolymer of hydroxyl-unit) such as hydroxybutyrates (HBs), hydroxyvalerates (HVs) and hydroxyhexanoates (HHs). Typically, SO mainly contains long-chain-fatty-acid (LCFA) with unsaturated fatty acid (C14:1 – C18:3) and therefore, the selected PHA-producer would be developed during unbalanced growth (feast-famine condition). Operation of the fed-batch for almost 6 months under aerobic dynamic conditions (with various operating conditions) has increased the PHA production up to 33% of dried cell weight. It was also shown that sludge subjected to aerobic condition in mixed cultures could accumulate high amount of PHA by manipulating the cycle length (HRT study). The high specific PHA storage rate (qpfeast = 0.5 C-mol/C-mol. h) as well as the high sludge PHA contents achieved by mixed cultures make this saponified SO competitive with those based on the other vegetable oil (e.g. corn oil, soy oil, etc.)